Last term - Cox, Pamela; Enid, Blyton (London : Hodder childern book, 2019)
In this final book about the girls at Malory Towers, Darrell becomes head girl. Unfortunately not all the girls are as responsible as she is and in her last term Darrell sees many changes in her old school friends
Keywords: English - Teenage fiction book